PENGARUH PEMAHAMAN PERATURAN PERPAJAKAN, TARIF PAJAK, DAN KUALITAS PELAYANAN TERHADAP KEPATUHAN WAJIB PAJAK (Studi Kasus pada Wajib Pajak Orang Pribadi Non Karyawan di KPP Pratama Cibinong Periode 2020) - Raharjo, Nabilla Karlinda; Majidah, Majidah; Kurnia, Kurnia (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.09.NO.07.TAHUN 2020, 2020)
Taxes are the source of state revenue which gives the biggest contribution in supporting the state budget. However, state revenue from taxes in Indonesia is not optimal. This optimization is due to the low level of compliance of taxpayers in carrying out their tax obligations. The purpose of this study was to determine the effect of understanding tax regulations, tax rates, and service quality on Taxpayers Obedience simultaneously and partially. Non-Employee Individual Taxpayers who are registered as SPT compliant in KPP Pratama Cibinong are the population in this study. This study uses convenience sampling with a total sample of 72 people. The data of this study were analyzed with descriptive statistical analysis and multiple linear regression analysis. The results showed that partially, only tax rates and service quality were affected by taxpayers obedience. While simultaneously, understanding taxation regulations, tax rates, and service quality affects the obedience of taxpayers.